2022
DOI: 10.1021/acs.jpclett.1c03530
|View full text |Cite
|
Sign up to set email alerts
|

Subpicosecond Hot Hole Transfer in a Graphene Quantum Dot Composite with High Efficiency

Abstract: Extraction of hot carriers is of prime importance because of its potential to overcome the energy loss that limits the efficiency of an optoelectronic device. Employing a femtosecond upconversion setup, herein we report a few picoseconds carrier cooling time of colloidal graphene quantum dots (GQDs) is at least an order of magnitude slower compared to that in its bulk form. A slower carrier cooling time of GQDs compared to that of the other semiconductor quantum dots and their bulk materials is indeed a covete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 88 publications
(130 reference statements)
3
15
0
Order By: Relevance
“…Excellent optical properties of our as-synthesized NCs are demonstrated by their sharper fwhm’s of PL bands (<22 nm), higher PLQYs (91–95%), and narrower size distributions, compared to that of conventional QDs, in good agreement with previous reports (Figure a–c). , The PL spectra of our NCs are even much sharper than that of the organic dye molecules, suggesting that our NCs have broader implication for display applications. TEM images revealed the cubical shapes of our NCs, characterized by narrow size distributions, and the respective particle sizes (edge lengths) were found to be ∼8.0 ± 0.8 nm (CsPbBr 3 ), ∼10.5 ± 1.1 nm (MAPbBr 3 ), and 10 ± 1 nm (FAPbBr 3 ) (Figure d–f). Powder X-ray diffraction (PXRD) studies further confirmed the cubic perovskite structures of all three NCs (Figure g–i).…”
Section: Results and Discussionsupporting
confidence: 90%
“…Excellent optical properties of our as-synthesized NCs are demonstrated by their sharper fwhm’s of PL bands (<22 nm), higher PLQYs (91–95%), and narrower size distributions, compared to that of conventional QDs, in good agreement with previous reports (Figure a–c). , The PL spectra of our NCs are even much sharper than that of the organic dye molecules, suggesting that our NCs have broader implication for display applications. TEM images revealed the cubical shapes of our NCs, characterized by narrow size distributions, and the respective particle sizes (edge lengths) were found to be ∼8.0 ± 0.8 nm (CsPbBr 3 ), ∼10.5 ± 1.1 nm (MAPbBr 3 ), and 10 ± 1 nm (FAPbBr 3 ) (Figure d–f). Powder X-ray diffraction (PXRD) studies further confirmed the cubic perovskite structures of all three NCs (Figure g–i).…”
Section: Results and Discussionsupporting
confidence: 90%
“…However, when FCDs was synthesized under harsh solvothermal conditions, the poorly characterized chromophoric byproducts are clumped into individual solid particles that are sometimes difficult to separate using membrane dialysis because of their strong associations with FCDs. We believe that the emissions from the latter type FCDs would be intrinsically excitation-dependent because of their multichromophoric nature. ,,, On the contrary, the former ones would mostly show single chromophoric emissions independent of the excitation wavelength after purification via membrane dialysis. , However, this notion is not always true, especially when more than one FCD subsets have been produced in the synthesis with similar sizes but different in their spectral identities, where excitation-dependent PL is inevitable despite the ideal chromophoric nature of the individual FCDs. , By exploiting polarity differences of the subsets, one may separate them into different batches using chromatographic methods and subsequent dialysis, as shown in Figure . This two-step purification method assures the highest integrity of the FCD samples, characterized by excitation independent PL as well as the uniform nature of their emission centers.…”
Section: Why Is Stringent Sample Purification So Important For Cds?mentioning
confidence: 99%
“…PL blinking of CDs observed in a single molecule study is another attractive property, suggesting the probable quantum nature of their emission states. Like metal chalcogenide quantum dots, PL blinking from single carbonaceous dots has been hypothesized with several phenomena: (i) hopping of quantum emission state to other states having either different PLQYs or absorption cross sections causing different brightness at the same excitation rate, (ii) trap state induced band-edge recombination, and (iii) Auger recombination in charged nanocrystals (i.e., trion formation). ,, Since blinking is detrimental to modern applications like optoelectronics, bioimaging, etc., substantial efforts have been put forward to unravel the underlying mechanism. Nevertheless, a universally accepted explanation is still missing.…”
Section: A Few Examples Showing Well-characterized Cds Are Promising ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the surface of QDs is highly reactive, , there is always a possibility of change of status of QDs in the presence of an externally added chemical analyte. Additionally, the strong fluorescence of QDs, which is due to the recombination of the bound electron and hole, may get easily perturbed in the presence of a chemical analyte and thus can induce a significant change in the photophysical outcome. ,, As the photogenerated exciton and its recombination stand as the main backbone for all the photovoltaic applications, a detailed investigation is necessary to elucidate the underlying mechanism of the interaction between QDs and analytes at the QD–analyte interface.…”
Section: Introductionmentioning
confidence: 99%